Profesionalisme Jurnalis Dalam Film The Bang-Bang Club (Studi Analisis Semiotika Ferdinand De Saussure) - Revaldo Dewa Fransisko, Indrawati, Ahmad Harun Yahya (CV. ITTC INDONESIA, 2023)
One of the definitions of film is moving images. Movies are often grouped together under the umbrella term